KCNT1‐related epilepsy: An international multicenter cohort of 27 pediatric cases. (13th March 2020) - Borlot, Felippe; Abushama, Ahmed; Morrison‐Levy, Nadine; Jain, Puneet; Puthenveettil Vinayan, Kollencheri; Abukhalid, Musaad; Aldhalaan, Hesham M.; Almuzaini, Hanin S.; Gulati, Sheffali; Hershkovitz, Tova; Konanki, Ramesh; Lingappa, Lokesh; et al.
Abstract: Objective: Through international collaboration, we evaluated the phenotypic aspects of a multiethnic cohort of KCNT1‐related epilepsy and explored genotype‐phenotype correlations associated with frequently encountered variants. Methods: A cross‐sectional analysis of children harboring pathogenic or likely pathogenic KCNT1 variants was completed. Children with one of the two more common recurrent KCNT1 variants were compared with the rest of the cohort for the presence of particular characteristics. Results: Twenty‐seven children (15 males, mean age = 40.8 months) were included. Seizure onset ranged from 1 day to 6 months, and half (48.1%) exhibited developmental plateauing upon onset. Two‐thirds had epilepsy of infancy with migrating focal seizures (EIMFS), and focal tonic seizures were common (48.1%). The most frequent recurrent KCNT1 variants were c.2800G>A; p.Ala934Thr (n = 5) and c.862G>A; p.Gly288Ser (n = 4). De novo variants were found in 96% of tested parents (23/24). Sixty percent had abnormal magnetic resonance imaging (MRI) findings. Delayed myelination, thin corpus callosum, and brain atrophy were the most common. One child had gray‐white matter interface indistinctness, suggesting a malformation of cortical development. Several antiepileptic drugs (mean = 7.4/patient) were tried, with no consistent response to any one agent. Eleven tried quinidine; 45% had marked (>50% seizure reduction) or some improvement (25%‐50% seizure reduction). Seven used cannabidiol; 71% experienced marked or some improvement. Fourteen tried diet therapies; 57% had marked or some improvement. When comparing the recurrent variants to the rest of the cohort with respect to developmental trajectory, presence of EIMFS, >500 seizures/mo, abnormal MRI, and treatment response, there were no statistically significant differences. Four patients died (15%), none of sudden unexpected death in epilepsy. Significance: Our cohort reinforces common aspects of this highly pleiotropic entity. EIMFS manifesting with refractory tonic seizures was the most common. Cannabidiol, diet therapy, and quinidine seem to offer the best chances of seizure reduction, although evidence‐based practice is still unavailable.